Pengembangan Pola Rithem Tradisi Minangkabau Dalam Proses Penggarapan Karya Musik Dream High - Afri Dino; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2021)
The use of traditional arts as a working medium in the creation of a musical work is one of the efforts to introduce traditional arts to